Aesthetic modernism and masculinity in fascist Italy - Champagne, John. (Popular culture and world politics, 2013)
"Aesthetic Modernism and Masculinity in Fascist Italy is an interdisciplinary historical re-reading of a series of representative texts that complicate our current understanding of the portrayal of masculinity in the Italian fascist era. Examining paintings, films, music and literature in light of some of the ideological and material contradictions that animated the regime, it argues that fascist masculinity was itself highly contradictory. It brings to the fore works that have tended to be under-studied, and argues that, while fascist inclusive strategies of patronage worked to bind artists to the regime, an official policy of non-interference may inadvertently have opened up a space whereby the arts expressed a more complicated and contestatory view of masculinity than the one proffered by kitsch photos of a bare-chested Mussolini skiing. Champagne seeks to evaluate how the aesthetic analysis of the artifacts explored offer a more sophisticated and nuanced understanding of what world politics is, what is at stake when something like 'masculinity' is rendered as being an element of world politics, and how such an understanding differs from more orthodox 'cultural' analyses common to international relations.Providing a significant contribution to understandings of representations of masculinities in modernist art, this work will be of great interest to students and scholars of gender studies, queer studies, political science, Italian studies and art history. "--